Wireless communication technology for wireless power transfer - McKay, Marnie Lianna (2018)
This project involves setting up, improving and implementing the wireless communications for a resonant wireless power transfer set-up in which the communications send data wirelessly from voltage monitoring sensors to regulate voltage levels to ensure they are correct and safe and other sensors for different purposes in the system. The project was carried out in NTU’s Rolls Royce EPSIL@N (Electrical Power Systems Integration Labs at NTU) to serve for their resonant wireless power transfer prototype. Improving speed performance and communicating correct data were the main focuses for the wireless communications since unsafe voltage levels need to be alerted and rectified quickly as well as correctly. Multi-channel communication was also a requirement due to there being multiple sensors. An initial literature review studies suitable communication protocol options and hardware for the communications. The current wireless resonant power transfer set-up and SPI communication which was implemented are also outlined. Firstly, the hard-ware was set up and improved via soldering the modules. The initial wireless communications speed was quantified via testing. Increasing this speed was then carried out with respect to any limitations and the communications was then adjusted and tested to ensure data was being received correctly. Lastly, multi-channel communication was implemented via software and communicated via the maximum number of channels (sixteen). After checking the communications functioned correctly, this project’s final wireless communications was then successfully implemented into the existing wireless power transfer set-up. Regulated wireless power transfer with wireless communication (consists of control signals and other data simultaneously) has been demonstrated.